3D Printing Additive Manufacturing - Sengottuvel, P. (International Journal of Psychosocial Rehabilitation, 2018)
In the recant years a new generation of machine is developed that can make everyday things, these machines are called 3D printers. They’re remarkable because they can produce different kinds of objects, in different materials, all from the same machine. 3D printing, also known as additive manufacturing (AM), in this process layers of material are formed under computer control to create an object. In 3D printing unlike material removed from a stock in the conventional machining process, 3D printing or AM builds a three-dimensional object from computer-aided design (CAD) model successively adding material layer by layer of material until the entire object is created. Each of these layers can be seen as a thinly sliced horizontal cross-section of the eventual object. To prepare a digital file for printing, the 3D modeling software “slices” the final model into hundreds or thousands of horizontal layers. When the sliced file is uploaded in a 3D printer, the object can be created layer by layer. The 3D printer reads every slice (or 2D image) and creates the object, blending each layer with hardly any visible sign of the layers, with as a result the three-dimensional object.